2002
DOI: 10.21273/jashs.127.4.515
|View full text |Cite
|
Sign up to set email alerts
|

T4 Lysozyme and Attacin Genes Enhance Resistance of Transgenic `Galaxy' Apple against Erwinia amylovora

Abstract: Genes encoding lysozyme (T4L) from T4 bacteriophage and attacin E (attE) from Hyalophora cecropia were used, either singly or in combination, to construct plant binary vectors, pLDB15, p35SAMVT4, and pPin2Att35SAMVT4, respectively, for Agrobacterium-mediated transformation of `Galaxy' apple, to enhance resistance to Erwinia amylovora. In these plasmids, the Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Explants were propagated in tissue culture as described by Norelli et al (1988) and Ko et al (2002), with root induction as described by Bolar et al (1998). Young trees were transferred to soil and grown in a greenhouse with Na vapor supplemental lighting to maintain the daylength at 16 h, and a maximum-minimum temperature range of 35/20°C.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Explants were propagated in tissue culture as described by Norelli et al (1988) and Ko et al (2002), with root induction as described by Bolar et al (1998). Young trees were transferred to soil and grown in a greenhouse with Na vapor supplemental lighting to maintain the daylength at 16 h, and a maximum-minimum temperature range of 35/20°C.…”
Section: Plant Materialsmentioning
confidence: 99%
“…With the target of increasing disease resistance to fungal pathogens, Bolar et al (2000Bolar et al ( , 2001 and Wong et al (1999) introduced a chitinase from Trichoderma harzianum into Marshall McIntosh and Royal Gala. The lytic proteins attacin and T4 lysozyme (Norelli et al 1994;Ko et al 2000Ko et al , 2002 and a modified cecropin MB39 gene (Liu et al 2001) were used to achieve enhanced resistance to fire blight, caused by the bacterium Erwinia amylovora.…”
Section: Regeneration and Transformationmentioning
confidence: 99%
“…Attacin, cecropin, and sarcotoxin genes, derived from different insect genomes, have been introduced in different plant species with promising results (Reynoird et al 1999;Ko et al 2000Ko et al , 2002Bespalhok Filho et al 2001). Transgenic potato (Solanum tuberosum L.) expressing cecropin and tobacco (Nicotiana tabacum L.) expressing shiva-1 genes (a cecropin synthetic analog) showed an increase in resistance to Ralstonia solanacearum Smith Yabuuchi et al (Montanelli and Nascari 1991;Jaynes et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Mansf.] expressing the basic attA form (Norelli and Aldwinckle 1993) as well as transgenic apple and pear (Pyrus communis L.) expressing the acidic attE form (Norelli et al 1994;Ko et al 2002;Reynoird et al 1999) showed a reduced susceptibility to fire blight Erwinia amylovora (Burr) Winslow et al…”
Section: Introductionmentioning
confidence: 99%